IMPLEMENTATION OF PUBLIC SERVICES MALL FOR THE COMMUNITY IN PALEMBANG CITY’ - Holipah Holipah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research is about the Implementation of Public Service Malls for the Community in Palembang City. However, in reality the MPP in Palembang City is not fully running well because there are still many complaints and complaints from the public to the government. The purpose of this research is to provide convenience, speed, affordability, security and convenience to the public in obtaining services. In addition to increasing global competitiveness in providing ease of doing business and obtaining facilities and infrastructure that can benefit recipients. This study used descriptive qualitative method. The research results show that, first of all, the low availability of human resources at MPP, the unavailability of comfortable facilities and infrastructure for recipients and the lack of socialization by the government regarding the existence of MPP in Palembang City. Based on the results of this study, it can be concluded that the implementation of MPP for the community in Palembang City has not been effective, those that have been well maintained and those that are still more or less improved, especially outreach to the community.